2022
DOI: 10.1111/dth.15391
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse reactions of COVID ‐19 vaccines: A systematic review

Abstract: Background: Numerous vaccines are implementation for the prevention of severe course and lethal outcome of coronavirus disease 2019 .Objective: This systematic review aims to summarize and integrated the ndings of studies regarding cutaneous side effects of COVID-19 vaccines.Methods: This systematic review conducted by searching the scienti c databases of PubMed, Scopus, Science direct, and Web of knowledge from the beginning of the COVID-19 to10/5/2021. Articles were reviewed and analyzed based on the Preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
(199 reference statements)
2
22
0
4
Order By: Relevance
“…As suggested by previous studies, rash and urticaria have been the most studied systemic skin reactions related to COVID-19 vaccines [ 31 ]. Moreover, local injection site reactions were one of the most prevalent reactions [ 53 , 54 ]. After vaccination, the human body generates an immune response; meanwhile, the inflammation in the muscle at the injection site may occur [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested by previous studies, rash and urticaria have been the most studied systemic skin reactions related to COVID-19 vaccines [ 31 ]. Moreover, local injection site reactions were one of the most prevalent reactions [ 53 , 54 ]. After vaccination, the human body generates an immune response; meanwhile, the inflammation in the muscle at the injection site may occur [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…After vaccination, the human body generates an immune response; meanwhile, the inflammation in the muscle at the injection site may occur [ 53 ]. These responses can contribute to the adverse skin reactions [ 54 ]. We found that the incidence rates of these systemic reactions were very low and that related concerns were unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These safe and effective vaccines have been associated with cutaneous reactions in a subset of patients.The most common cutaneous reactions are delayed injection site reactions involving redness, swelling, pain, or induration that occur within 7 days following vaccination. 2,3 Most reactions are self-limiting and do not require treatment. More rare vaccine reactions include urticaria, morbilliform eruptions, pityriasis rosea, and vasculitis.…”
mentioning
confidence: 99%
“…More rare vaccine reactions include urticaria, morbilliform eruptions, pityriasis rosea, and vasculitis. 2,3 In one large review of 40,640 patients who received mRNA vaccines, urticaria involving itchy wheels occurred in 0.3% of patients after the first vaccine dose…”
mentioning
confidence: 99%